Identifikasi Mutu Fisik Sediaan Sabun Padat Kulit Buah Pisang Ambon dan Aktivitasnya terhadap Staphylococcus epidermidis - Basir, Hernawati; Zulfahmi Hamka; Sunarti; Hardianti; A. Tenriugi Daeng Pine (Universitas Islam Negeri Alauddin Makassar, 2023)
The processing of bananas is limited to the utilization of the fruit, so that it produces waste in the form of the skin. Basically, this banana rinds waste can be used as an ingredient for making traditional product preparations. This is because the banana rind contains several chemical compounds that have properties. Banana rinds contains glycosides, saponins, tannins, and flavonoids that can inhibit pathogenic bacteria so that it can be used as an antibacterial. To increase the use value of banana rinds waste, further processing is needed, for example in the manufacture of soap preparations.flavonoids that can inhibit pathogenic bacteria so that it can be used as an antibacterial. To increase the use value of banana rinds waste, further processing is needed, for example in the manufacture of soap preparations. This study aims to determine the physical quality of the formulation of bar soap from the ethanol extract of Ambon banana rinds (Musa paradisiaca Var. Savientum (L.) Kunt) concentrations of 5% (F1) and 10% (F2). In this study, the physical quality of soap preparations were tested in the form of organoleptic tests, namely color, odor, and shape, pH test, foaming power test, and hardness test. The ethanol extract of Ambon banana rinds was obtained by maceration method and then formulated into solid soap preparations. Based on the research, the results showed that the preparation of bar soap from the ethanolic extract of banana rinds with a concentration of 5% (F1) and 10% (F2) met the physical quality test, namely organoleptic F1 and F2 had a dark brown color, a distinctive odor and had a solid shape, pH soap preparations F1 9 and F2 8, the height of foam for soap preparations F1 and F2 is 100 mm, and the hardness test for soap F1 is 0.6 scale and F2 is 0.5 scale.